Isolation, molecular characterization and pathogenicity studies of infectious bursal disease field virus isolates - M. M. Amer (Journal of Veterinary Medical Research, 2018)
This study was carried out to investigate the prevalence, molecular characterization and pathogenicity of field infectious bursal disease virus (IBDV) isolates. Nine isolates of IBDV were isolated from 13 naturally infected broiler flocks. Detection of IBDV antigen was carried out by agar gel precipitation test (AGPT), followed by virus isolation in specific pathogen free (SPF) embryonated chicken eggs (ECE) and finally molecularly characterized and identified using reverse transcriptase polymerase chain reaction (RT-PCR). The obtained nine strains of IBDV by RT-PCR were further classified by using restriction fragment length polymorphism (RFLP) technique into (4) classical, (3) variant and (2) very virulent (vv) IBDV serotype (I). The pathogenicity of the isolated IBDV strains was detected by three passages in SPF ECEs and by experimental infection of one hundred 14 days old maternally immune layer chicks. The results showed that the mortality rate of the embryos was increased by increase the number of passages till the third passage where it reached 100% for all IBDV strains and the embryos showed typical lesions of IBDV. Chicks inoculated with variant IBDV strains showed morbidity rates of 60-80 %, without mortalities. Sacrificed birds showed atrophied bursae and thymus glands and enlarged thickened proventriculus. Groups infected with classical IBDV strains showed morbidity rates 40- 60,% with mortality 0-20%. The detectable lesions were muscular hemorrhages with variable bursal lesions. Inoculated chicks with vvIBDV strains showed 50-70% morbidity and mortality of rate was 30% with lesions of muscular hemorrhages, severe nephrosis with ureates in the ureters, hemorrhagic bursitis and pin point hemorrhages on the proventricular glands. Control negative non-infected group showed neither clinical signs nor mortalities along the observation period. The histopathological effect (lesion score) of IBDV strains on the bursa, spleen and thymus glands confirmed the previously mentioned results and revealed that the highest severity (score) for these organs were induced by vv IBDV strains.